2013
DOI: 10.1111/jan.12298
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the psychometric properties and theoretical grounding of instruments evaluating self‐care in people with type 2 Diabetes Mellitus

Abstract: There are no instruments for identifying self-care behaviours or barriers elaborated with a strong validation process. Further research should be carried out to provide patients, clinicians and researchers with valid and reliable instruments that are methodologically solid and theoretically grounded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 70 publications
2
62
0
7
Order By: Relevance
“…Another systematic review was conducted on self-reported instruments assessing selfcare in patients with type 2 diabetes, which identified 16 instruments. Again, relevant methodological limitations were found by authors in all the validation studies, questioning the validity and reliability of the instruments (Caro-Bautista et al 2014). Another review identified 19 selfreported instruments developed to evaluate self-care in people with hypertension, which revealed there was no selfcare instrument rigorously evaluated for its measurement properties that covered all the behavioural domains important for people with high blood pressure (Han et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another systematic review was conducted on self-reported instruments assessing selfcare in patients with type 2 diabetes, which identified 16 instruments. Again, relevant methodological limitations were found by authors in all the validation studies, questioning the validity and reliability of the instruments (Caro-Bautista et al 2014). Another review identified 19 selfreported instruments developed to evaluate self-care in people with hypertension, which revealed there was no selfcare instrument rigorously evaluated for its measurement properties that covered all the behavioural domains important for people with high blood pressure (Han et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The methodology used and the results of this literature review have been presented elsewhere (Caro‐Bautista et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…and the absence of a theoretical model on which to solidly develop the items that will comprise the measurement instrument (Caro‐Bautista et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Systematic review studies 14 - 15 ) have highlighted the lack of instruments for the assessment of self-care behavior in people with DM2.…”
Section: Introductionmentioning
confidence: 99%